Smilax auriculata A new host for Orchid fleck dichorhavirus identified in Florida, USA - Dey, Kishore (Plant disease, 2021)
In June 2020, Orchid fleck virus (OFV) was detected in a species of Liriope in Leon and Alachua County, Florida (Fife et al; 2021). In October of the same year, four adjacent dune/ear-leaf greenbrier vines, Smilax auriculata (Smilaceae: Liliales), showed yellowing and mottling symptoms (Figure 1). Infected and healthy S. auriculata leaves samples were collected in Alachua County by the Florida Department of Agriculture and Consumer Services, Gainesville, Florida. OFV primers successfully detected in four Smilax samples by conventional RT-PCR assay. Amplicon sequences (Acc. No. MZ645935 and MZ645938) shared 99% nucleotide identity with OFV infecting orchids (LC222629) and citrus (MK522804). The OFV subgroup I (OFV-Orc1) and subgroup II (OFV-Orc2) specific primers (Kondo et al 2017) were utilized to confirm the presence of OFV type strains infecting Smilax. Sanger sequencing of subgroup I specific amplicons (MZ645934) shared 99% nucleotide identity with OFV-Orc1 (LC222629) whereas subgroup II specific amplicon sequence (MZ645930) shared 98-99 % nucleotide identity with OFV-Orc2 (AB244417). Further confirmation was done by USDA-APHIS-PPQ-Plant Pathogen Confirmatory Diagnostics Laboratory utilizing optimized conventional RT-PCR protocols (Roy et al. 2020) and deep sequencing on a on a NextSeq550 Illumina platform. Assembled reads identified seven non-overlapping viral contigs. Five RNA1 and two RNA2 contigs covered more than 97% of the bipartite OFV genome with average coverage depth of 5297.61 and 5186.04, respectively. Contigs of RNA1 and RNA2 shared 98-99% nt identity to OFV-Orc2-RNA1 (AB244417) and OFV-Orc-RNA2 (AB244418 and LC222630). No other pathogen sequences were identified. This is the first time the genus Smilax has been identified as a natural host of OFV. Very recent findings of OFV-Orc in Florida in Liriope, Aspidistra, and Ophiopogon among the Asparagaceae family members (Fife et al; 2021) and now in the Smilacaceae suggest a broader host range of the virus than previously known; further research should be conducted to better characterize the potential risk of introduction into citrus in Florida